Documented and Undocumented Skilled Mexican Immigrants and the Global Recession in Los Angeles Metropolitan Region - Fabiola Galicia Bretón Mora; Rafael Alarcón Acosta (Norteamérica)
The main purpose of this article is to analyze the labor market integration of documented and undocumented skilled Mexican immigrants in Los Angeles Metropolitan region during the global recession of 2008. To this end, we use a mixed methodological approach. From the quantitative perspective, we analyze data from the American Community Survey. The qualitative approach includes 20 open-ended interviews with Mexican skilled immigrants. The main findings reveal that skilled immigrants were not negatively affected by the global recession. In addition, legal immigration status turned out to be the most important factor in differentiating those who obtained a skilled occupation and those who did not. However, some immigrants, including those who were undocumented, were able to strategically use their investment in human capital and their access to professional social networks in order to obtain professional occupations.